New adapiform primate fossils from the late Eocene of Egypt. (17th February 2018) - Seiffert, Erik R.; Boyer, Doug M.; Fleagle, John G.; Gunnell, Gregg F.; Heesy, Christopher P.; Perry, Jonathan M. G.; Sallam, Hesham M.
Abstract: Caenopithecine adapiform primates are currently represented by two genera from the late Eocene of Egypt ( Afradapis and Aframonius ) and one from the middle Eocene of Switzerland ( Caenopithecus ). All are somewhat anthropoid-like in several aspects of their dental and gnathic morphology, and are inferred to have been highly folivorous. Here we describe a new caenopithecine genus and species, Masradapis tahai, from the 37 million-year-old Locality BQ-2 in Egypt, that is represented by mandibular and maxillary fragments and isolated teeth. Masradapis is approximately the same size as Aframonius but differs in having a more dramatic distal increase in molar size, more complex upper molar shearing crests, and an exceptionally deep mandibular corpus. We also describe additional mandibles and part of the orbit and rostrum of Aframonius which suggest that it was probably diurnal. Phylogenetic analyses place Masradapis either as the sister taxon of Aframonius (parsimony), or as the sister taxon of Afradapis and Caenopithecus (Bayesian methods). Bayesian tip-dating analysis, when combined with Bayesian biogeographic analysis, suggests that a common ancestor of known caenopithecines dispersed to Afro-Arabia from Europe between 49.4 and 47.4 Ma, and that a trans-Tethyan back-dispersal explains Caenopithecus ' later presence in Europe. For Masradapis :https://www.zoobank.org/urn:lsid:zoobank.org:act:41BC8459-7CCE-487F-BC59-1C34257D5C4E For Masradapis tahai :https://www.zoobank.org/urn:lsid:zoobank.org:act:C0A620AD-6FCA-4649-A980-FCA237AFE39D